Assessment of cadmium and lead in organic and conventional root and tuber vegetables from Serbian market - Savić, Jasna (Journal of Agricultural Sciences (Belgrade), 2022)
The aim of research was to determine and to compare cadmium (Cd) and lead (Pb) concentrations in organic and conventional root and tuber vegetables from Serbian market. Samples of three root and tuber vegetables commonly consumed in Serbia including potato, carrot and beetroot were collected at two green markets and three supermarkets at the territory of Belgrade. Concentrations of Cd and Pb in fresh weight were determined by AAS. Means were compared by t-test. Cd and Pb concentrations in both types of vegetables were bellow allowable limits. Potato mean Cd concentration was significantly lower in organic than in conventional type (0.021 mg kg-1 and 0.037 mg kg-1, respectively), whilst in carrot it was the opposite, but differences between the two were types were not significant, including beetroot. Results indicated lower Pb level in organic potato and beetroot, and higher Pb level in organic carrot, but differences between means were not significant in all tested vegetables. Obtained results are no conclusive, but they indicate a lower concentration of both metals in organic root and tuber vegetables.